Assess the Knowledge and Practice on Nesting of New Born among Postnatal Mothers with a View to Prepare Information Booklet. - Sreeletha, Arunima; Rajendra Salunke, Dipali; Eknath Sasane, Maheshwari; Dattatray Waingankar, Prajkta; Kishor Kamble, Rushabh; Suresh Ghadge, Sandhya; Ramsubhavan Rajak, Santosh (International Journal of Nursing Research, 2023)
Background: Maintaining thermoregulation is very vital for newborn babies in the immediate newborn period and continues until the first half of infancy. Different thermoregulation techniques should be followed traditionally by mothers for the same. Objectives: The objectives of the study were to assess knowledge and practice on nesting among postnatal mothers, find out the association between selected demographic variables and knowledge. Materials and Methods: This study was a descriptive survey method. The study was conducted at selected hospital in Navi Mumbai in 120 postnatal mothers. Non-probability purposive sampling was used. Tools include sociodemographic and clinical data, knowledge questionnaire, and observational checklist. The tool reliability score is 0.9. Results: Frequency distribution of demographic data was calculated. Demographic data reveal that there is an association between age, education, and number of postnatal days with knowledge regarding nesting. Knowledge level regarding nesting among postnatal mothers represents that only one mother has excellent knowledge, 11 have good knowledge, 80 have adequate, and 28 have poor knowledge regarding nesting. Practice on nesting among postnatal mothers represents that 11 mothers have good practice on nesting, 99 are average, and 10 are having poor practice regarding nesting. From finding the researchers found out that knowledge and practice regarding nesting of newborn among postnatal mothers are average. Conclusion: As hypothermia is the leading cause of death in neonates, thermoregulatory measures have been recommended by heath-care members. Hence, the present study was conducted to assess knowledge and practice on nesting of newborn among the postnatal mothers to prevent hypothermia.